HUBUNGAN PRENATAL YOGA DENGAN KECEMASAN PADA IBU HAMIL DALAM MENGHADAPI PERSALINAN DI KLINIK SANTA ELISABETH TAHUN 2019 - RAMATIAN SIMANIHURUK; METERIA SIMBOLON; KRISTINA AQUILINA NAHAK (JURNAL EKONOMI, SOSIAL & HUMANIORA, 2020)
Methods to relieve and help pregnant women in preparation for childbirth are exercise that aims to maintain the health of the body and fetus so that it develops properly and also keeps the mother’s emotions stable, namely walking, cycling, swimming, pregnancy exercise, hypnobirthing, and yoga. The aim of the study was to determine the relationship between prenatal yoga and anxiety in pregnant women in facing childbirth at the Santa Elisabeth Kefamenanu Clinic. This type of research is quantitative with a cross sectional research design. The population in this study were all pregnant women who took 110 prenatal yoga classes while the sample in this study was 110 respondents. Sampling by Total Sampling. Data collection using a questionnaire sheet. Data analysis used chi-square test and multiple logistic regression. The results showed that the variables that had a relationship with maternal anxiety in facing childbirth were prenatal yoga (p=0.001), work (p=0.028), parity (p=0.006), family support (p=0.009). The dominant factor related to anxiety about childbirth was prenatal yoga (OR= 3,503). The conclusion of this study is that prenatal yoga can prevent anxiety in pregnant women